2021
DOI: 10.3390/brainsci11060781
|View full text |Cite
|
Sign up to set email alerts
|

Factors Predicting Ictal Quality in Bilateral Electroconvulsive Therapy Sessions

Abstract: In electroconvulsive therapy (ECT), ictal characteristics predict treatment response and can be modified by changes in seizure threshold and in the ECT technique. We aimed to study the impact of ECT procedure-related variables that interact during each session and might influence the seizure results. Two hundred and fifty sessions of bilateral ECT in forty-seven subjects were included. Seizure results were evaluated by two different scales of combined ictal EEG parameters (seizure quality index (SQI) and seizu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 60 publications
(121 reference statements)
1
2
0
Order By: Relevance
“…However, our results are at odds with the results of Belz et al, 16 who found that serum sodium levels had an effect on interhemispheric coherence in a prospective trial with 31 patients. Comparable with their study and in line with other studies, 13,14,17 we also consistently found significant effects of age and dose on seizure quality markers. One possible explanation for the differing results is the larger sample size and larger serum electrolyte level variability in the present study.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, our results are at odds with the results of Belz et al, 16 who found that serum sodium levels had an effect on interhemispheric coherence in a prospective trial with 31 patients. Comparable with their study and in line with other studies, 13,14,17 we also consistently found significant effects of age and dose on seizure quality markers. One possible explanation for the differing results is the larger sample size and larger serum electrolyte level variability in the present study.…”
Section: Discussionsupporting
confidence: 92%
“…These include younger age and better physical status. 14 To date, only few studies have examined the role of serum electrolyte levels on seizure quality, with available studies yielding conflicting results. A retrospective study of 207 patients undergoing ECT found no correlation between baseline sodium and seizure threshold or seizure duration at their first ECT session.…”
mentioning
confidence: 99%
See 1 more Smart Citation